(untitled) - Madlenakova, Lucia (Doprava a spoje, 2007)
The paper talks about problemacy of telecommunication operator's position assessment on a world market. The paper includes position analysis of certain operators on a world market according to telecommunication service income and near profit. Comparing the selected years of operators, the evaluation of telecommunication market dynamics for a longer period and there is also a concentration level in telecommunication branch settled according to Herfindahl - Hirschman's index.